Determinant of Sharia Bank's Financial Performance during the Covid-19 Pandemic - Reza Nurul Ichsan; Sudirman Suparmin; Mohammad Yusuf; Rifki Ismal; Saleh Sitompul (Budapest International Research and Critics University, 2021)
Financial performance as a measuring instrument to know the process of implementing financial resources owned by the company. The Covid-19 pandemic has impacted the banking sector, resulting in poor financing due to debtors' disbursements as a result of the large number of people losing their jobs and difficulties in financing payments. This research aims to analyze the financial performance of Islamic Banks during the Covid-19 pandemic, using records of annual financial statements from 2011 to 2020 through Multiple Linear Regression testing and linearity testing of the model used ramsey test. As a result of this study, the results of the t test found that the Capital Adequacy Ratio (CAR), Operating Costs to Operating Income (BOPO), Financing to Deposit Ratio (FDR) had a positive and significant effect on financial performance (ROA) while Not Performing Financing (NPF) had a negative and insignificant effect on financial performance (ROA). Furthermore, simultaneously capital adequacy ratio (CAR), Operating Costs to Operating Income (BOPO), Financing to Deposit Ratio (FDR) and Not Performing Financing (NPF) significantly influenced the financial performance (ROA) of Sharia banks in Indonesia.